Аналіз фінансового стану підприємств машинобудівної галузі - Годес, О.Д. (Культура народов Причерноморья, 2013)
У статті проведено оцінку фінансового стану підприємств машинобудівної галузі.
Проведена оцінка фінансових результатів діяльності машинобудівних підприємств за 2006 – 2011 рр.
Наведено динаміку об'ємів реалізації продукції машинобудівних підприємств за аналізуємий період.
Представлена динаміка показників рентабельності операційної діяльності підприємств цієї галузі.
Визначено наступні проблеми машинобудівних підприємств: різну розмірність фінансових коефіцієнтів;
відсутність універсальної методики трактування якісних показників управління фінансовою діяльністю
підприємств. В статье представлена оценка финансового состояния предприятий
машиностроительной отрасли. Проведена оценка финансовых результатов деятельности
машиностроительных предприятий за 2006 - 2011 гг. Приведена динамика объемов реализации
продукции машиностроительных предприятий за анализируемый период. Представленна динамика
показателей рентабельности операционной деятельности предприятий этой отрасли.
Определены следующие проблемы машиностроительных предприятий: разная размерность финансовых
коэффициентов, отсутствие универсальной методики трактовки качественных показателей
управления финансовой деятельностью предприятий. In this article it is presented the assessment of the financial situation of machine-building industry
enterprises.
It is shown the estimation of financial performance of the machine-building enterprises in 2006 - 2011.It is
shown the dynamics of products sale volume for machine building enterprises analysed period. It is presented
dynamics of indicators of profitability of enterprises' operating activity in this area.
It is determined that the most successful machine building enterprises activity was in 2011, when the overall
financial result was 14.4 bln., In prior years the industry has achieved the best result in 2007, in this period
financial result of machine building enterprises was 5.128 billion . UAH.
It is proved that in recent years the share of sold products in the machine-building enterprises in common
industrial production was hovering around 10 - 14%. For example, in 2011 it was 12.03%, while in 2001 -
10.21%. Level of profitability of machine building enterprises began to decline from the end of 2008, due to the
crisis. In 2011, profitability indicators of mechanical engineering is not only significantly improved in relation
to 2010, but also to the all analyzed period.
It is identified the following problems of mechanical enterprises: different dimension of financial ratios; lack of
universal methods of enterprises' qualitative financial management interpretation.